2021
DOI: 10.1186/s12882-021-02578-6
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the relationship between quality of life and hope in family caregivers of hemodialysis patients and related factors

Abstract: Background Family caregivers of hemodialysis patients are the first and most crucial source of care at home. They experience many problems in the care of hemodialysis patients, which can affect their quality of life and hope, affecting the quality of care provided to patients. This study aimed to determine the relationship between quality of life and hope in family caregivers of hemodialysis patients. Methods A cross-sectional (descriptive-analytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 35 publications
(40 reference statements)
1
7
0
2
Order By: Relevance
“…In terms of the correlation of age with QOL, our study revealed that there was a negative correlation between the age and QOL of the caregivers, implying that with increased caregiver age his QOL decreases. This can be clarified by the normal physiologic process of aging This result is in line with a study done by (Sajadi et al, 2021) which was performed on 300 family caregivers in the east of Mazandaran province in Iran. Revealed that there was a reverse and significant correlation between the age of caregiver with the variable of caregivers' quality of life (P < 0.001) using short form (SF8).…”
Section: Discussionsupporting
confidence: 85%
“…In terms of the correlation of age with QOL, our study revealed that there was a negative correlation between the age and QOL of the caregivers, implying that with increased caregiver age his QOL decreases. This can be clarified by the normal physiologic process of aging This result is in line with a study done by (Sajadi et al, 2021) which was performed on 300 family caregivers in the east of Mazandaran province in Iran. Revealed that there was a reverse and significant correlation between the age of caregiver with the variable of caregivers' quality of life (P < 0.001) using short form (SF8).…”
Section: Discussionsupporting
confidence: 85%
“…This study also showed a positive association between monthly caregiving and caregiver burden, the longer care, the higher caregiver burden. The results of a study on hemodialyzers in Iran similarly revealed that the burden of care increases with the amount of time caregivers provide care [ 48 ]. Also, the findings of studies in Western countries have found that the longer time the caregiver spends with the patient was found to be a predictor of greater burden experienced by the caregivers, and by increased duration of disease, the primary caregiver experienced greater burden.…”
Section: Discussionmentioning
confidence: 99%
“…Komorbiditas berdampak buruk terhadap kelangsungan hidup pasien hemodialisa. Kondisi ini berdampak negatif pada kelangsungan hidup serta kualitas hidup dalam menjalankan hemodialisa (Sajadi et al, 2021). Faktor-faktor yang dapat mempengaruhi kualitas hidup pada pasien hemodialisa antara lain faktor sosial demografi seperti jenis kelamin, usia, suku, pendidikan, status pernikahan, lama terapi, pekerjaan, dan efikasi diri (Anees et al, 2018).…”
Section: Pendahuluanunclassified